Isolation and Characterization of L-Asparaginase Producing Endophytic Fungi from Plants of the Amaryllidaceae Family - Asri Setiani Kadir; A. Mu’thi Andy Suryadi; Mahdalena Sy. Pakaya; Faramita Hiola; Wiwit Zuriati Uno (Universitas Muhammadiyah Palu, 2026)
L-asparaginase is an enzyme that catalyzes the conversion of L-asparagine into L-aspartate and inhibits the growth of leukemia cells that depend on asparagine. This study aims to isolate and characterize endophytic fungi from plants of the Amaryllidaceae family, and to evaluate the ability of these isolates to produce the L-asparaginase enzyme. This study employed an experimental method conducted in a pharmaceutical microbiology laboratory. Endophytic fungi were isolated using surface sterilization techniques, followed by cultivation on Potato Dextrose Agar (PDA) media. Enzyme production was performed in liquid fermentation, whereas enzyme purification was conducted using ammonium sulfate fractionation with concentrations of 0–20%, 20–40%, 40–60%, 60–80%, and 80–100%. The activity of L-asparaginase enzyme was tested using the Nesslerization method, with Asparagus used as an inducer. The findings showed that several endophytic fungal isolates produced L-asparaginase, as indicated by a yellowish-brown color in the Nessler test. The purified fractions exhibited varying enzyme activities at different levels of ammonium sulfate saturation. Therefore, endophytic fungi from plants of the Amaryllidaceae family have potential as alternative sources of the L-asparaginase enzyme, which can be further developed in pharmacy and biotechnology.